Modulation of floral development by a gibberellin-regulated microRNA. - Achard, P; Herr, A; Baulcombe, D; Harberd, N (2004)
Floral initiation and floral organ development are both regulated by the phytohormone gibberellin (GA). For example, in short-day photoperiods, the Arabidopsis floral transition is strongly promoted by GA-mediated activation of the floral meristem-identity gene LEAFY. In addition, anther development and pollen microsporogenesis depend on GA-mediated opposition of the function of specific members of the DELLA family of GA-response repressors. We describe the role of a microRNA (miR159) in the regulation of short-day photoperiod flowering time and of anther development. MiR159 directs the cleavage of mRNA encoding GAMYB-related proteins. These proteins are transcription factors that are thought to be involved in the GA-promoted activation of LEAFY, and in the regulation of anther development. We show that miR159 levels are regulated by GA via opposition of DELLA function, and that both the sequence of miR159 and the regulation of miR159 levels by DELLA are evolutionarily conserved. Finally, we describe the phenotypic consequences of transgenic over-expression of miR159. Increased levels of miR159 cause a reduction in LEAFY transcript levels, delay flowering in short-day photoperiods, and perturb anther development. We propose that miR159 is a phytohormonally regulated homeostatic modulator of GAMYB activity, and hence of GAMYB-dependent developmental processes.